Mainstream and Margins: An exploration of the policy, practice and perspectives that have shapred part-time flexible learning in Irish Higher Education 2012-18 - Hunt, Nuala (Trinity College Dublin. School of Natural Sciences. Discipline of Botany, 2020)
Part-time flexible learning in Irish higher education has not been embedded within mainstream policy and was of marginal interest to policy makers and Higher Education Institutions (HEIs’). This subject also received limited attention from Irish based researchers. In contrast, Irish Higher Education (HE) policy, research and funding focused on full-time mainstream traditional (ie 18-22 year olds) students. In this regard Irish HE was not unique as similarities can be found internationally. In Ireland there was a lack of growth in part-time numbers which was linked to the absence of free fees and the inability to access grants. In the aftermath of the banking crisis of 2008, there was renewed interest in part-time flexible HE. Another perspective emerged as the national strategy for HE was launched in 2011. From this perspective HE needed to reform in order to provide more flexible part-time programmes to cater for adults who wished to up-skill, reskill and participate in the labour market. As part of this agenda the labour market activation scheme Springboard was introduced offering free places on HE programmes, many of which were part-time. Yet this 2011 over-view overlooked what was a more complex narrative about part-time flexible HE which from a range of perspectives, required unpacking. This case study explored the relationship between policy and practice, involving key stakeholders; policy makers, lecturers and students. Tinto’s (1973) theory of integration provided a framework for analysis of student retention and persistence. During 2015-18, one hundred and two participants took part in semi-structured interviews, including policy-makers (n=9), lecturers (n=30) students (n=63). The key research questions informing the study were; (1) To what extent was HE policy informed by lifelong learning policy? (2) What was driving current interest in part-time flexible learning? (3) What were lecturer’s experiences of teaching and supporting part-time flexible (PTF) students? (4) Similarly what motivated students, what factors constrained and enhanced their experience? (5) Also what was their sense of belonging and integration within HEIs, and why they persisted in their studies? The data generated indicated a less straightforward interpretation of a neglected dimension of HE. Lifelong learning was a wide-ranging but slippery concept which had become orientated toward ‘learning for earning’ as public policy emphasised widening participation for the purposes of ensuring economic growth. Also as state funding had reduced, some HEIs had expanded PTF learning in an effort to generate much needed revenue. Findings indicated funding remained a key problem but without any immediate solution to what was a political issue. Some indicators from the data demonstrated an effort to make PTF learning visible as the HEA commenced counting part-time students and signalled changes to the recurring grant allocation model. Nevertheless there was no data for part-time progression or retention no understanding of student persistence. Lecturers observed that PTF students were diverse, motivated, committed and appeared to complete their programmes. The student profile and timing of programmes required active and experiential approaches to teaching. Students were goal orientated and in many cases that goal was to complete the programme and gain the qualification. Students’ sense of belonging and inclusion varied across HEIs’. Whilst few students noted a sense of inclusion many indicated they belonged though this was associated with the; class group, programme, department or school. Findings also indicated access to supports and facilities remained a problem where PTF students were concerned. Tinto’s theory of academic and social integration did not translate to PTF students who were not homogeneous they presented as adults with multiple responsibilities coupled with temporal constraints limiting their ‘integration’ within HEI’s. Nevertheless findings suggested PTF students persisted. Theories of integration fall short where diversity was encountered and whilst inclusion may be a better fit evidence indicated that Irish HEIs’ were unable to sustain inclusive environments for PTF students.
APPROVED
Keywords: Part-time, Flexible, Irish Higher Education; lifelong learning; policy, practice and perspectives